Spiritual Coping Strategies to Reduce Academic Stress: a Phenomenological Study of Emerging Adulthood among PAI Students - Nova Nur A'ini; Nurul Wahdah; Surawan Surawan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Spiritual coping strategies are an important approach in helping students reduce academic stress in emerging adulthood. This study aims to identify the factors contributing to academic stress among PAI students at IAIN Palangka Raya, understand how to deal with it through spiritual coping strategies, and understand the factors that influence spiritual coping. This study used a qualitative approach of phenomenology type, with the subjects being 7 PAI students from the batches of 2020, 2021, and 2022. Data were collected through semi-structured interviews, which are in-depth interviews to explore participants' experiences, views and perceptions. Data validation was conducted using member checking techniques, then analyzed through three stages: data condensation, data presentation, and conclusion drawing or verification. The results showed that the main factors affecting academic stress of PAI students at IAIN Palangka Raya include anxiety about one's ability, parents' expectations, competition with friends, task load, and tight class schedule. The spiritual coping strategies used are self-directing, deferring, and collaborative. Meanwhile, the success of spiritual coping strategies was influenced by education, life experience, and maturity of thinking. This study shows that integrating spiritual aspects is essential in helping students deal with academic stress in an Islamic education environment, and can serve as a basis for designing spiritual-based mentoring or counseling programs in religious tertiary institutions. The practical implication of these findings is that Islamic educational institutions need to develop curricula, guidance services, and mentoring programs that explicitly accommodate spiritual approaches in dealing with academic pressure, in order to create a more supportive and holistic learning environment for students.